PENGARUH LEVERAGE, SIZE, NPL, BOPO dan LDR TERHADAP KINERJA KEUANGAN BANK (STUDI PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014) - Haryati, Rina; Widyarti, Endang Tri (Diponegoro Journal of Management, 2016)
This study have purposed to identify and analyze the effect of leverage, size, NPL, BOPO and LDR of financial performance (ROA) in the general conventional banks period 2010 – 2014. Leverage has been proxied by the Short Term Debt to Total Asset (STDTA) and Long Term Debt to Total Asset (LTDTA).  The population  used in this study are conventional  commercial  banks that have been listed in the BEI at period 2010 – 2014. Sampling method for this study is using purposive sampling with 19 banks. This study uses multiple linear regression analysis with classic assumption test, descriptive statistics test, t statistical test, f statistical test and coefficient of determination test. The result on this study indicate that STDTA and NPL have no significant effect on ROA. LTDTA and BOPO have a negative significant effect on ROA. Size and LDR have positive significant effect on ROA.  The results  from  this study that BOPO  is the most influence  independent  variabel  to dependent  variabel  (ROA)  by statistical  t-test.  While  NPL  is the most  uninfluence  independent variable to dependent variable (ROA). This study is expected to be a consideration in the decision making of the company to improve the company's financial performance, especially in banking.